Corporate Regulation and Corporate Governance of Small Businesses in Australia - Heenetigala , Kumudini; Armstrong , Anona; Clarke , Andrew (Journal of Law and Governance, 2011)
This paper presents the results of a study of small business owner /managers and CEOs of industry associations in relation to corporate regulation and corporate governance for small businesses in Australia. It is part of a larger project investigating regulation and small business governance supported by an Australian Research Council grant and COSBOA. A survey of the CEOs of small business associations and small business owner/managers investigated the corporate governance practices of small businesses, their understanding of their duties as directors, their approach to managing risks and accountability, the regulatory difficulties experienced by small businesses, and the factors that inhibited or promoted the performance of small business.